2022
DOI: 10.1080/21655979.2021.2016088
|View full text |Cite
|
Sign up to set email alerts
|

Homeodomain-containing gene 10 contributed to breast cancer malignant behaviors by activating Interleukin-6/Janus kinase 2/Signal transducer and activator of transcription 3 pathway

Abstract: Homeodomain‑containing gene 10 (HOXC10) has been identified as an oncogene in various malignancies. Nevertheless, the role and function of HOXC10 in breast cancer (BC) remain unclear. RT-qPCR and Western blot were used to detect the mRNA and protein levels of genes, respectively. CCK-8, transwell, and TUNEL assays were performed to evaluate cell viability, invasion, migration, and apoptosis of BC cells in vitro. The xenograft model was established to examine the effect of HOXC10 on tumor growth in vivo. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The overexpression of HOXC10 in breast cancer is related to drug resistance to chemotherapy (Sadik et al, 2016) and a positive correlation between immune cell infiltration and poor prognosis in BRCAs . Methylation of the HOXC10 promoter, resulting in transcriptional repression, has been shown to contribute to resistance to endocrine therapy in estrogen receptor-positive breast cancer (Pathiraja et al, 2014) In addition, studies have demonstrated that HOXC10 can promote tumor growth in BRCA by upregulating the level of IL-6 to activate the JAK2/STAT3 signal transduction pathway (Shen et al, 2022). HOXC10 expression is dysregulated in various cancers, acting as a carcinogenic driver associated with poor prognosis (Bao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of HOXC10 in breast cancer is related to drug resistance to chemotherapy (Sadik et al, 2016) and a positive correlation between immune cell infiltration and poor prognosis in BRCAs . Methylation of the HOXC10 promoter, resulting in transcriptional repression, has been shown to contribute to resistance to endocrine therapy in estrogen receptor-positive breast cancer (Pathiraja et al, 2014) In addition, studies have demonstrated that HOXC10 can promote tumor growth in BRCA by upregulating the level of IL-6 to activate the JAK2/STAT3 signal transduction pathway (Shen et al, 2022). HOXC10 expression is dysregulated in various cancers, acting as a carcinogenic driver associated with poor prognosis (Bao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of HOXC10 in breast cancer is related to drug resistance to chemotherapy ( Sadik et al, 2016 ) and a positive correlation between immune cell infiltration and poor prognosis in BRCAs ( Zhang et al, 2022 ). Methylation of the HOXC10 promoter, resulting in transcriptional repression, has been shown to contribute to resistance to endocrine therapy in estrogen receptor-positive breast cancer ( Pathiraja et al, 2014 ) In addition, studies have demonstrated that HOXC10 can promote tumor growth in BRCA by upregulating the level of IL-6 to activate the JAK2/STAT3 signal transduction pathway ( Shen et al, 2022 ). HOXC10 expression is dysregulated in various cancers, acting as a carcinogenic driver associated with poor prognosis ( Bao et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, up-regulation of HOXC10 has been found in many types of human malignant solid tumors that occur in the head and neck, lung, breast, stomach, liver, and ovary. It has been reported to promote tumorigenesis through oncogenic pathways, angiogenesis, release of inflammatory cytokines, immunosuppressive effects, and the activation of epithelial mesenchymal transition (EMT)-related genes [ 14 , 16 , 19 , [33] , [34] , [35] ]. The results of these studies indicate that HOXC10 may play an oncogenic role in driving tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%